H3K79me3T80ph is a Novel Histone Dual Modification and a Mitotic Indicator in Melanoma - Danielle R. Martinez; Hunter W. Richards; Qiushi Lin; Carlos A. Torres-Cabala; Victor G. Prieto; Jonathan L. Curry; Estela E. Medrano (Journal of Skin Cancer)
The current study characterizes the mitosis-associated histone dual modification on the core of histone H3: trimethylation of histone H3 lysine 79 and simultaneous phosphorylation of H3 threonine 80 (H3K79me3T80ph). Through the use of protein and microscopy-based techniques, we find that H3K79me3T80ph shares a similar spatial and temporal regulation as H3S10ph but additionally requires methyltransferase activity. In addition, we find that Aurora kinase activity is necessary for the catalysis of H3K79me3T80ph in vivo. Finally, our analysis of H3K79me3T80ph using a tissue microarray indicates that H3K79me3T80ph marks a subset of primary cutaneous melanomas with metastatic potential indicating that H3K79me3T80ph may identify a subset of invasive melanomas with a more aggressive clinical behaviour.